STRATEGI WRITING WORKSHOP UNTUK MENINGKATKAN KEMAMPUAN MENULIS PARAGRAF MAHASISWA JURUSAN BAHASA DAN SASTRA INGGRIS - Trisanti, Novia (Universitas Negeri Semarang, 2011)
This study is about the use of Writing Workshop as a strategy in Paragraph Based Writing (PBW) class to improve studentsâ ability in writing a paragraph. The statement of the problems in this study are (1) how Writing Workshop strategy can be used in PBW class to improve the ability of 3 semester English department students of Unnes in writing a paragraph, and (2) whether the use of Writing Workshop can change the students attitude when they are asked to write a paragraph. Its aim is to describe how writing workshop strategy can be used to improve the ability of 3 rd semester English department students of Unnes to write a paragraph. The research methodology was Classroom Action Research (CAR), which was done in two cycles. Each cycle consists of four meetings. In those cycles, the students involved in all activities of writing workshop startegy, such as mini lesson, writing time, sharing (authorâs chair), and writing celebration. In cycle one, the material was about narrative texts. In cycle two, the material was about expository texts. The result showed that there was an improvement in the studentsâ scores between pre test and post test scores. It was 39.25. Another good results could be seen from the observation and interview. The studentsâ understanding of the materials was good. Their writing of a paragraph got better constantly. For example, the ideas were getting better, the organization of paragraph was correct, the appropriatteness of grammar and diction was accurate, also the mechanics were good. Besides, the students were more motivated.